Pola Komunikasi Interpersonal Kakak Damping Campus Sosial Responsibility Unitomo Periode 2017 - Wulandari, Suryati (Jurnal Komunikasi Profesional, 2018)
Campus Social Responsibility is a Surabaya government’s program as an effort to save the children who have social welfare problems in Surabaya. The aim of this program is to rescue the children who almost and already dropout of their school by making them to get an education like the other children. CSR involves  the students from civitas academica of universities in Surabaya. The students from third semester until sixth semester who can attend CSR program because it hopes that they are able to identify and solve the problem of them.  The type of this research is descriptive qualitative analysis by using interpersonal communication analysis by Joseph A. Devito. The writer uses the depth interview techniques as data collection techniques, and literature studies because the technique makes it possible to extract data.Keywords: Patterns, Interpersonal Communication, Unitomo CSR Assistance 2017